INDEPENDENSI AUDITOR, ETIKA AUDIT DAN KUALITAS AUDIT - Elfreda Aplonia Lau (Prodi Ilmu Administrasi Negara, 2018)
Independence, Audit Ethics And Audit Quality.The aim to review the influence of Auditor independence, Audit Ethics or Professional Auditor's Ethics on Audit Quality. The assessment was conducted descriptively with reference to the studies that have been done. Based on the review, it is known that independence as an independent variable has a significant effect on audit quality, on the other hand independence has no significant effect on audit quality.Auditor independence affects the quality of the audit if the auditor is able to uphold or maintain its independence. It’s cna be achieved if the auditor in performing his duties is guided by the audit standards established by the Indonesian Institute of Accountants – Ikatan Akuntansi Indonesia’ (IAI), that is the general standards, standard field work and reporting standard. Conversely, the independence of the auditor does not affect the quality of the audit if the independence of the auditor is weakened. The weakening of the auditor's independence is due to the conflict of power of role such as the client can suppress the auditor against professional standards and in large measure, a healthy client's financial condition can be used to suppress the auditor by making the auditor's replacement.This may make the auditor unable to withstand the pressure of the clientThe ethics of the auditor may be placed as an independent variable affecting audit quality and other findings show the ethics of the auditor as independent variable, not affecting the quality of audit. While the result of others research find that the auditor ethics is placed as a moderating variable that moderates the influence of independence on audit quality and moderates the influence of competence on audit quality.Overall, it can be said that the influence of attitude toward the behavior, subjective norm and perceived behavioral control on intention in determining individual behavior is determined by intention to behave. The amount of influence attitude toward the behavior, subjective norms and perceived behavioral control can vary from individual to individual